Decarbonization of space heating in the Italian Alpine context: Thermo-economic assessment of the levelized energy cost of heating under alternative renewable scenarios - Lorenzo Menin; Gregorio Borelli; Alessandro Prada; Giovanni Pernigotto; Andrea Gasparella; Marco Baratieri (Energy Conversion and Management: X)
The decarbonization of the built environment represents a priority in Europe and requires intervening on energy use for space heating. Although recent strategies have often relied on heat electrification through heat pumps, their effectiveness can be limited in mountain regions due to low temperatures. Nevertheless, mountain contexts offer opportunities for heat decarbonization through bioenergy, as well as other off-the-shelf renewable solutions such as photovoltaics. In this study we conduct a thermo-economic assessment of four scenarios for the near-full electrification of space heating in residential dwellings in South Tyrol, within the coldest Italian climatic zone. Two scenarios rely on biomass gasification combined heat-and-power and (1) air-source or (2) district heat and water-source heat pumps, and two are based on rooftop photovoltaic with air-source heat pumps, (3) with or (4) without battery storage. The results show that scenarios (1), (3) and (4) reduce complementary natural gas consumption to 17.9 % of the total heat energy delivered, while scenario (2) allows eliminating it completely. However, scenario (1) exhibits the highest competitiveness under recent subsidization policies, with a weighted average levelized energy cost of heat of 104 €/MWh, in line with the cost of standalone natural gas combustion in condensing boilers. PV delivers the second most cost-effective solution with strong improvement potential under grid electricity cost reductions. The study shows that current economic conditions already allow for levelized energy costs of heat close to competitiveness with natural gas and delivers useful preliminary results while offering a replicable methodology for the assessment of similar case studies.